Change Health Analysis: A Framework for Evaluating the Readiness and Integration of Change Enablers - Tourista, Meiko; Sutanto, Eddi; Azwir, Akbar (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
- The successful delivery of organizational change is an inherently complex endeavor, determined overwhelmingly by the readiness and ability of the human capital to adopt new ways of working. High-profile studies consistently indicate that the primary driver of change failure is the inadequate management of the "people side," often manifesting as a deficit in key structural enablers rather than flawed strategy. This study addresses a significant methodological gap: the failure of traditional execution methods to quantify and integrate the health of the three critical and interdependent functional pillars necessary for change success: Sponsorship, Project Management, and Change Management. This paper introduces the Change Health Analysis (CHA) framework, developed as an integral component of the overarching ENGAGE Star Change Model. The CHA is a diagnostic tool designed to overcome the limitations of siloed metrics by providing a quantified, integrated view of change readiness. The framework systematically assesses the strength and balance of the three core enablers (Sponsorship, Project Management (PM), and Change Management (CM)) through three distinct scorecards. Each scorecard detailing five specific assessment factors. The total score for each role is then translated into a clear health indicator (e.g., Excellent, Need Attention, Need Immediate Action) to facilitate timely and targeted intervention plans. By operationalizing the evaluation of these key enablers, the CHA offers a novel, non-proprietary contribution that enables change leaders to identify high-risk areas and proactively develop targeted action plans before execution begins.